Current status of cesarean section myomectomy-prospective ongoing study - Bala, Ripan; Kamal, Preet; Nagpal, Madhu; Singh, Sheena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of the study was to assess the feasibility, safety and efficacy of performing myomectomy during cesarean section. Methods: It was prospective study conducted in Sri Guru Ram Das University of Health and sciences which is a tertiary care referral centre. Myomectomy was conducted in 34 pregnant women during elective or emergency cesarean section. Analysis was done with reference to age, parity, character of myomas, intraoperative and post-operative morbidity, duration of surgery and duration of stay in hospital. Results: In this study 34-58 fibroid of various size (2-14 cm) were removed in 34 patients during cesarean section. Majority of fibroids were located in body of uterus (65.5%) and in anterior wall (55.2%) and all them were sub serosal. No significant difference was found in mean preoperative hemoglobin (11.8±0.7) and postoperative hemoglobin (10.9±0.8). No patient had postpartum hemorrhage requiring cesarean hysterectomy. Only two patient needed blood transfusion postoperatively. Mean time taken for surgery was 58.4±8.94 minute and average duration of hospital stay was 6.7±1.6. Conclusions: With the advent of better anesthesia, easy availability of blood and blood component, cesarean myomectomy is safe surgical procedure when performed by experienced obstetrician in carefully selected patients.